Analisa Pengaruh Perubahan Pemakaian Uang Kartal Ke Uang Giral Terhadap Perilaku Konsumen - Wening Purbatin Palupi Soenjoto (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
Money is the second means of payment after the barter pattern that was carried out in the days before the discovery of coins in the VII century BC. Along with the times, the way of barter changed. People exchange goods using symbols or objects. The function of these objects is close to the function of money, but many people find it difficult to determine and determine such exchange rates. Finally, people know exchange with currencies. Technological sophistication is able to change the pattern of money and currency usage into demand deposits which are considered easier and more efficient. Money becomes the current payment instrument for all buying and selling transactions both directly and indirectly. money as a means of payment, as a means of payment of debt, as a hoarding tool or transfer of wealth (capital), and a tool to improve social status. The government's policy began to impose demand deposits as legal tender and began to be widely used by the wider community. With the ease of use of demand money makes it easy for people to make transactions and economic activities which in turn can affect consumer behavior in using demand deposits.